Macroeconomic Determinants and Green Assets in Explaining Stock Return Dynamics: Evidence from Indonesia - Nurdina, Nurdina; Nurkholis, Nurkholis; Adib, Noval; Atmini, Sari (International Journal of Energy Economics and Policy, 2026)
This study examines the effects of macroeconomic variables—interest rates, inflation, and exchange rate fluctuations—on green stock returns in Indonesia, highlighting the moderating role of green assets. Using firm-level data from 111 companies listed in the ESG Quality 45 Index (IDX KEHATI) during 2021–2023, the analysis integrates macroeconomic fundamentals with sustainability-linked financial indicators to capture market sensitivity to economic shocks. The results reveal that interest rates and inflation exert negative and statistically significant effects on green stock returns, while exchange rate fluctuations are insignificant. Green assets, however, enhance market performance and resilience, particularly under inflationary conditions. The positive interaction between inflation and green assets indicates that sustainability-oriented investments serve as an effective hedge against inflation. The model explains approximately 42% of the variation in returns and remains robust across lagged estimations. These findings extend the Arbitrage Pricing Theory by incorporating sustainability-based risk factors grounded in the Fisher Effect and Green Premium Hypothesis, emphasizing the strategic importance of green finance in strengthening market stability and supporting the transition toward a low-carbon economy.